Bioinspired Fingertip for Anthropomorphic Robotic Hands. Issue 1 (23rd July 2014) - Controzzi, Marco; D'Alonzo, Marco; Peccia, Carlo; Oddo, Calogero Maria; Carrozza, Maria Chiara; Cipriani, Christian
Abstract : Background: An artificial fingertip with mechanical features and appearance similar to the human fingertip could represent a significant step forward towards the development of the next generation artificial hands. However, so far, a fingertip showing a good trade-off among mechanical features, appearance and anthropomorphism, along with its 3D computational model, is still missing. Objective: To explore and develop an artificial fingertip demonstrating a mechanical response similar to the human fingertip, in order to improve the grasp stability of robotic hands. Methods: Taking inspiration from the multi-layered structure of the human finger, novel artificial fingertips, composed of a rigid core and covered by layers of polymeric materials with different degrees of stiffness and topped by a hard nail were developed. An accurate 3D finite element (FE) model was also developed in order to simulate and evaluate the internal mechanical behavior of the prototypes under external indentations. The mechanical response of the prototypes was assessed and compared with that of the human fingertip and the FE model results, under different experimental conditions. Finally, the artificial fingertips were integrated into an anthropomorphic robotic hand and evaluated in grip tests, in order to compare the grasp stability with respect to conventional stiff (metal) fingertips. Results: The developed prototypes demonstrated a response to compression tests similar to the human finger and the FE model showed a discrete accuracy (mean error 7%). Finally, an increased ability (by 96%) in stably holding objects during precision grips with respect to conventional stiff fingers was demonstrated. Conclusion: Multi-layered biomimetic fingertips can improve grasp stability and cosmetic appearance of anthropomorphic robot hands.